A case of alpha-fetoprotein–producing adenocarcinoma of the endometrium with a hepatoid component as a potential source for alpha-fetoprotein in a postmenopausal woman. Issue 3 (1st April 2006) - Takeuchi, K.; Kitazawa, S.; Hamanishi, S.; Inagaki, M.; Murata, K.
Abstract : Although case reports of alpha-fetoprotein (AFP)–producing adenocarcinoma other than hepatocellular carcinoma have gradually increased in number, AFP-producing adenocarcinoma of the endometrium is very rare. The patients universally complain of abnormal vaginal bleeding. The patient presented with complaints of epigastric discomfort. No vaginal bleeding was observed. Serum AFP concentration was 453 ng/mL, and lens culinaris agglutinin–reactive AFP percentage of total AFP was increased to 67%. Radiologic imaging and endoscopy did not provide evidence of any primary carcinoma in the liver and gastrointestinal tract. To investigate the unknown origin of high AFP, Pap smear of the endometrium followed by fractional curettage was performed and revealed adenocarcinoma of the endometrium. Radical hysterectomy with pelvic lymph node dissection and partial omentectomy was performed. Histologic study showed a mixture of major AFP-negative endometrioid adenocarcinoma and minor medullary proliferation of the AFP-positive hepatoid adenocarcinoma cells with eosinophilic cytoplasm and hyaline globules. After the surgery followed by four courses of weekly carboplatin and paclitaxel administration, serum levels of AFP dropped into normal range. The possible existence of AFP-producing adenocarcinoma of the endometrium should be considered in a postmenopausal woman even if there is no vaginal bleeding, when AFP-producing tumor is clinically suspected and the imaging studies fail to confirm the diagnosis.